2022
DOI: 10.1371/journal.pgph.0000563
|View full text |Cite
|
Sign up to set email alerts
|

The role of family planning counselling during maternal and child health services in postpartum modern contraceptive uptake in Ethiopia: A national longitudinal study

Abstract: Family planning counselling can help improve the postpartum modern contraceptive uptake. However, studies in Ethiopia indicate inconsistent effects of integrated family planning counselling on postpartum modern contraceptive uptake. This study aimed to determine the extent of family planning counselling and its role in improving postpartum contraceptive uptake among women in Ethiopia. We used the Performance Monitoring for Action (PMA) Ethiopia panel survey data, a community-based prospective cohort study. Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(54 reference statements)
3
8
1
Order By: Relevance
“…Expanding service integration, including FP integration could be one of the e cient strategies to achieve these agenda. Existing evidence consistently support the effectiveness of FP integration with other services in increasing use of FP and reducing unmet need for FP (8,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding service integration, including FP integration could be one of the e cient strategies to achieve these agenda. Existing evidence consistently support the effectiveness of FP integration with other services in increasing use of FP and reducing unmet need for FP (8,15).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of FP integration with HIV care services reported improvement in FP uptake and declines in unmet need for FP among women of reproductive age group with HIV infection (13,14). A longitudinal study also demonstrated that FP counselling during postpartum and during child immunization period were associated with increased modern contraceptive uptake (15). However, integration of FP with other PHC services is still not strong (16).…”
Section: Introductionmentioning
confidence: 99%
“…Expanding service integration, including FP integration could be one of the efficient strategies to achieve these agenda. Existing evidence consistently support the effectiveness of FP integration with other services in increasing use of FP and reducing unmet need for FP [ 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of FP integration with HIV care services reported improvement in FP uptake and declines in unmet need for FP among women of reproductive age group with HIV infection [ 20 , 21 ]. A longitudinal study also demonstrated that FP counselling during postpartum and during child immunization period were associated with increased modern contraceptive uptake [ 22 ]. However, integration of FP with other PHC services is still not strong [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women in Ethiopia who state an intent to use contraception during the postpartum period are likely to have previous knowledge and/or experience of contraception (Abraha, Teferra, and Gelagay 2017; The Ethiopian Ministry of Health (MOH) has thus recommended that postpartum family planning be fully integrated into maternal health services, so that "every new mother will leave the clinic having made an informed choice about family planning," (Ministry of Health 2020:28). An important component of the guidelines to integrate PPFP into maternal health services is quality counseling, which does seem to impact contraceptive uptake, even though rates of counseling remain low in Ethiopia (Mruts et al 2022). The MOH advises healthcare providers to engage in discussions with expectant mothers during antenatal care visits on PPFP, including contraceptive counseling.…”
mentioning
confidence: 99%